Phenomenological approach to the modelling of elliptical galaxies: The problem of the mass-to-light ratio - Samurović S. (Serbian Astronomical Journal, 2007)
In this paper the problem of the phenomenological modelling of elliptical galaxies using various available observational data is presented. Recently, Tortora, Cardona and Piedipalumbo (2007) suggested a double power law expression for the global cumulative mass-to-light ratio of elliptical galaxies. We tested their expression on a sample of ellipticals for which we have the estimates of the mass-to-light ratio beyond ~ 3 effective radii, a region where dark matter is expected to play an important dynamical role. We found that, for all the galaxies in our sample, we have α + β > 0, but that this does not necessarily mean a high dark matter content. The galaxies with higher mass (and higher dark matter content) also have higher value of α+β. It was also shown that there is an indication that the galaxies with higher value of the effective radius also have higher dark matter content. .